Gustav Wilmanns, ein Schüler Mommsens, an der Kaiserlichen Universität Dorpat (1869–1872) - von Ungern-Sternberg, Jürgen (Hyperboreus, 2014)
Gustav Wilmanns (1845–1878) worked only four years (1869–1872) at Dorpat/Tartu University. The author reconstructs this period of his life, examining the archive data and Wilmanns’ letters in order to depict the university climate, professors and authorities of that time and the inevitable formalities of the public service in Russia.